Peningkatan Regulasi Emosi Melalui Bimbingan Kelompok dengan Teknik Permainan Kartu Zona Emosi - Cantika Adelia Kusuma; Isfauzi Hadi Nugroho; Lely Yuanita (CV. ITTC INDONESIA, 2025)
Emotion regulation is the ability of individuals to manage, control, and adjust their emotions in various situations. The results of direct observation in class XI-G SMAN 1 Kediri show that there are still many students who have low emotion regulation skills with an average of 51.8. This study aims to determine the improvement of emotion regulation ability of students in class XI SMAN 1 Kediri through group guidance services with emotion zone card educational game techniques. The research was carried out in two cycles with a total of three meetings, starting from the pre-cycle, followed by cycle I, and cycle II. Each cycle consists of four stages: planning, implementation, observation, and reflection. The subjects of the study were eight students from class XI-G with low levels of emotion regulation. The results showed a significant increase in emotion regulation ability, with an average of 47.8 at pre-cycle, increasing to 53.1 in cycle I, and reaching 58.1 in cycle II. This shows the success of group guidance services with emotion zone game techniques to improve students' emotion regulation skills.